Perilaku Pengguna Tik Tok di Kota Palopo dan Respon al-Qur’an - Serli R.; Abdul Mutakabbir; Ependi P. (Islamic Religious Education Departement, 2022)
Tik Tok is a new platform that young people love, and kids are no exception. This platform encompasses all levels of society, including adults and even the elderly. TikTok has both positive and negative sides like any other medium. Therefore, this study aims to determine the understanding of the community, especially the people of Palopo, about the benefits of Tik Tok and how to use it. This research is a field study with the people of Palopo city as informants for interviews and documentation. As a result, Tik Tok is used more than a means of entertainment, which sometimes leads to verbal and physical disrespectful behaviour. Some opinions say that Tik Tok is an online media short video that shows recordings of dancing and showing TikTok-er's genitals. The people of Palopo city consider TikTokers more for entertainment filled with dancing. Therefore, it is necessary to limit access to various media, including TikTok, so as not to be carried away by immoral behaviour. Thus, the Qur'an is the key and a solution to protect yourself by not showing your aurat. It means that Tik Tok may dive without showing aurat and indulgence in lust. For further researchers, it is necessary to research the effects caused by the application and the solution before and after being exposed to the syndrome.